2005
DOI: 10.1097/01.ta.0000198350.15936.a1
|View full text |Cite
|
Sign up to set email alerts
|

The Trauma Registry as a Statewide Quality Improvement Tool

Abstract: VSTR data indicate that the statewide trauma system is working well and provides a method for ongoing monitoring and trauma care feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 17 publications
5
75
0
5
Order By: Relevance
“…This finding is similar to the results of another study which showed that the highest frequency of victims belonged to men (82%) (Ghadipasha, Salari, Zarenezhad, Dehghanpour, & Gharedaghi, 2013). Regarding the age range of the injured people, the findings are in line with the results of other similar studies conducted in Iran (Cameron et al, 2005;Nizamo, Meyrowitsch, Zacarias, & Konradsen, 2006;Adib Zadeh, Ghadi Pasha, & Bastani, 2011;Ghadipasha, Salari, Zarenezhad, Dehghanpour, & Gharedaghi, 2013). It is notable that the age range of 20-39 can be the best years of life to be productive and generate income.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is similar to the results of another study which showed that the highest frequency of victims belonged to men (82%) (Ghadipasha, Salari, Zarenezhad, Dehghanpour, & Gharedaghi, 2013). Regarding the age range of the injured people, the findings are in line with the results of other similar studies conducted in Iran (Cameron et al, 2005;Nizamo, Meyrowitsch, Zacarias, & Konradsen, 2006;Adib Zadeh, Ghadi Pasha, & Bastani, 2011;Ghadipasha, Salari, Zarenezhad, Dehghanpour, & Gharedaghi, 2013). It is notable that the age range of 20-39 can be the best years of life to be productive and generate income.…”
Section: Discussionsupporting
confidence: 81%
“…The main reasons for pedestrian injuries can be poor decisions or risky behaviors during road crossings (Hashemiparast et al, 2016). In another study conducted in Australia, the researchers found that riders, passengers, and pedestrians were the most vulnerable victims (Cameron et al, 2005). Similarly, the findings of a study in China showed that motorcyclists, bicycle riders, and pedestrians were the most victims of traffic collisions (Qi, Yang, Qi, Zhang, & Wang, 2006 is notable that motorcycle collisions and their related injuries are major problems in developing countries (Heydari et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…14 The VSTR captures data about all major trauma patients across the state of Victoria (population 5 million) from all phases of trauma care. 15 A case is defined as a major trauma if the patient meets any of the following criteria: (1) death caused by injury; (2) Injury Severity Score (ISS) Ͼ15; (3) an intensive care unit (ICU) stay Ͼ24 hours and requiring mechanical ventilation; and (4) urgent surgery (intracranial, intrathoracic, intra-abdominal, or fixation of pelvic or spinal fractures).…”
Section: Victorian State Trauma Registrymentioning
confidence: 99%
“…The Victorian State Trauma Registry (VSTR) collects data on all major trauma patients in the state. 15,16 Patients registered by the VSTR meeting the following criteria were included in this retrospective study: a date of injury between July 2007 and June 2011; definitive management at the adult MTS hospitals; and those with a severe pelvic ring fracture defined as an Abbreviated Injury Scale (AIS) 17 pelvic fracture coded as 852606.4, 852608.4, or 852610.5.…”
Section: Methodsmentioning
confidence: 99%